WEAR BEHAVIOR OF PLASMA-SPRAYED PARTIALLY-STABILIZED ZIRCONIA ON A STEEL SUBSTRATE - AHN, HS; KWON, OK (ELSEVIER SCIENCE SA LAUSANNE, 1993)
In this experimental investigation, various layers of partially stabilized zirconia (PSZ) coated on steel by plasma spraying were studied to gain a better understanding of the tribological behaviour of PSZ under the conditions of dry contact in a reciprocating motion at a temperature of 200-degrees-C, which represents the severe operating conditions of friction pairs, such as cylinder liner-piston ring. The parameters investigated in relation to the wear behaviour were the thickness of the coating, oscillating frequency, sliding cycle and applied load. To identify the wear mechanism, X-ray diffraction, scanning electron microscopy and optical microscopy were used. In comparison with a steel-steel pair, PSZ coating-steel and PSZ coating-PSZ coating pairs exhibit far better wear characteristics and, therefore, the distinct possibility of applying a plasma-sprayed PSZ coating as a cylinder liner has been confirmed. The oscillating frequency and applied load conversely affect the wear rate of disc. The recommended coating thickness was found to be in the range 180-300 mum to ensure good anti-wear behaviour without the expense of high coating cost.